Care and social support from family and community in patients with pulmonary tuberculosis in Pakistan. Issue 4 (30th October 2019) - Saqib, Shahab E; Ahmad, Mokbul Morshed; Panezai, Sanaullah
Abstract : Objectives: This study aimed to validate the Medical Outcome Study–Social Support Survey (MOS-SSS) instrument in Pakistan and to quantify the nature of care and social support currently extended to patients with pulmonary tuberculosis (TB) in Pakistan. Design: This is a cross-sectional study design conducted within a period of 3 months from 1 November 2016 to 31 January 2017. Participants: A total of 269 patients, registered at 11 TB centres and private clinics, were interviewed through an interviewer-administered questionnaire. Main outcome measures: Cronbach's alpha was used to measure the internal consistency and reliability of the MOS-SSS survey instrument. Univariate and multivariable logistic regressions have been used to explore the association between care and social support, and socioeconomic factors. Result: This study validated the use of the MOS-SSS among patients with TB in Pakistan. Findings of the study revealed significant differences among the socioeconomic groups of patients in each subscale of social support. Additionally, results of logistic regressions showed that patients who were older (adjusted OR=6.17, 95% CI 1.55 to 24.59, p≤0.01), male (adjusted OR=2.73, 95% CI 1.49 to 4.98, p≤0.01), widow (adjusted OR=0.17, 95% CI 0.04 to 0.80, p≤0.05), and had a larger household size (adjusted OR=5.69, 95% CI 1.32 to 24.65, p≤0.05), higher monthly income (adjusted OR=2.00, 95% CI 1.11 to 3.60, p≤0.05) and house ownership (adjusted OR=1.99, 95% CI 1.10 to 3.60, p≤0.05) were significant factors associated with the extent of care and social support that the participants received. Conclusion: To cure TB, this study suggests a coordinated approach that includes not only clinical services to address this issue but also a strong social support system based on family and community necessary throughout the treatment process.